Pemanfaatan Media Sosial Instagram Sebagai Media Promosi Pada Akun Instagram @bittersweet_by_najla - Millenia, Leza Putri; Gemiharto, Ilham; Risanti, Yuliani Dewi (Telangke:Jurnal Telangke Ilmu Komunikasi, 2023)
This study aims to find out the reasons for the use of Instagram social media by Bittersweet by Najla, how it is used as a form of promotional activity, to the constraints on its use. This study uses a qualitative method with a case study approach and uses data collection techniques by interviews, observation, and documentation,. The key informants in this study are consist of two informants, with two informants as the main informant, and there is also four informants as supporting informants from Instagram followers of @bittersweet_by_najla as well as consumers and Instagram followers of @bittersweet_by_najla who are not consumers. Then, data analysis uses the Miles & Hubberman analysis technique which consist of three things, data reduction, data presentation, and conclusion/verification. The results of the study show that there are several reasons driving the use of Instagram social media by Bittersweet by Najla as a promotional medium, cost efficiency, easy operation and maximum features, the right social media platform to do promotion in the culinary field, fit Bittersweet by Najla's market segmentation, and the promising advertising features (Instagram Ads). Then it is also found in the management of Instagram social media Bittersweet by Najla which studies by use of Chris Heuer's Social Media Marketing concept with four elements in it namely context, communication, collaboration, connection it was found that the management of Instagram Bittersweet by Najla fulfilled these four elements as promotional media. However, it was found that these four elements complement each other, if there is one element that is not optimal it will affect the decline in sales and the existence of Bittersweet by Najla in the community. In addition, obstacles were also found in this study. This research is expected to produce an Instagram social media model for culinary businesses in order to promote a bussinesses.